Empowering diabetes care: Patient practices and the role of mobile health – A qualitative exploration - Jayvardhan Singh; Ramesh Kumar Sangwan; Shiv Kumar Mudgal; Ramesh Kumar Huda (Dialogues in Health, 2025)
Introduction: Effective diabetes management relies on medical treatment and self-care practices, yet many individuals face challenges in adhering to prescribed routines. With the rise of mobile health (mHealth), there is potential to enhance self-management through regular reminders, guidance, and support. This qualitative study explores patient practices in managing diabetes and the role of mHealth in influencing their behaviours and outcomes. Methodology: The study employed semi-structured, in-depth interviews with 14 individuals living with diabetes who had received SMS reminders and utilized the feedback application services as part of their diabetes management. Participants got education regarding self-care routines, including medication adherence, diet, exercise, and blood glucose monitoring. Thematic analysis was conducted to identify patterns related to diabetes management practices, patient challenges, and the role of mHealth. Results: Participants expressed positive feedback on the SMS and app-based services, which promote medication adherence and provide valuable health information. Challenges in diabetes management include physical limitations, social pressures leading to dietary lapses, time constraints, and concerns about receiving spam or misleading information via SMS. However, they recommended improvements, such as guidance on treatment, dietary advice, and the inclusion of interactive features like sugar level tracking. Conclusion: mHealth has the potential to enhance diabetes self-management significantly, and patient feedback suggests a need for more personalised, interactive, and comprehensive support. Addressing these recommendations alongside patients' physical, social, and financial challenges could improve health outcomes and foster more effective diabetes management.